Abstract ID: 368 Imaging radiologico a contrasto di fase e a conteggio fotonico. (December 2018) - Taibi, A.
Abstract : An introduction to novel imaging modalities, which take advantage of energy and phase characteristics of X-ray quanta will be here provided. X-ray detection in medical imaging typically involves an integration of the spectrum of X-rays exiting a patient, weighted by the detector's energy response. This procedure yields information related to the average energy of the spectrum exiting the patient, which for many clinical applications is sufficient. The spectral imaging methods allow instead the form, or shape, of the X-ray distribution exiting the patient to be measured [1]. In particular, energy-sensitive photon-counting detectors allow for further improvements of the diagnostic information by optimising the signal-to-noise ratio, anatomical background subtraction or quantitative analysis of object constituents [2]. Phase-contrast imaging has had an undeniable impact in the field of X-ray imaging during the last decades, and one of the main advantages lies in the fact that the phase shifting effects are related to characteristic properties of materials that are different from the ones involved in conventional X-ray imaging (i.e. the well-known absorption-contrast imaging) [3]. The mechanism that allows one to produce and to detect images according to this physical phenomenon will be here discussed, together with a review of main phase-contrast imaging techniques. Finally, the potential of both phase-contrast and spectral imaging in diagnostic radiology will be presented by means of specific applications.